eRASSt J040515.6-745202: A new X-ray transient discovered by eROSITA - Rau, A.; Grotova, I.; Gokus, A.; Haberl, F.; Liu, Z.; Schramm, M.; Homan, D.; Koenig, O.; Kreykenbohm, I.; Krumpe, M.; Maggi, P.; Vasilopoulos, G.; et al. (The Astronomer's Telegram, 2021)
During the third all-sky survey (eRASS3), the eROSITA instrument (Predehl et al. 2021) aboard the Russian/German Spektrum-Roentgen-Gamma (SRG) mission (Sunyaev et al. 2021) discovered a new X-ray transient, designated as eRASSt J040515.6-745202, and located in the Magellanic Bridge at: RA(J2000)= 04:05:15.30 (61.31456 deg) DEC(J2000)= -74:51:58.1 (-74.86683 deg) with an estimated positional uncertainty of ~5" radius (incl.
Keywords: Transient